Nature and Pattern Of Primary Teeth Extraction Among Children In Chennai City With Early Childhood Caries - SANKAR, PAVITHIRAA; MANI, GEO; RAVINDRAN, VIGNESH (The journal of contemporary issues in business and government, 2021)
Early childhood caries still remains as one of the main reasons for extractions in children. Many studies have been carried out on the extraction pattern of primary teeth in children, not much information is available regarding its outcome in the Indian population. So this study was aimed at investigating the frequency and type of the primary tooth extracted and the pattern of extraction in the South Indian population. This was a private hospital based retrospective study. The dental records of pediatric patients who had visited the dental hospital located in Chennai, Tamil Nadu, India from June 2019 to March 2020 were reviewed. Patients who underwent extraction of at least one primary tooth under local or general anesthesia were included in the study. Out of the total of 652 teeth extraction, 351 were of males and 301 females with the most common tooth extracted being the primary upper central incisor (35.53%) at 6 years (43.23%). Chi square test was done to assess the significance of association and there was a significant difference in the tooth extracted with age (p=0.00) and gender (p<0.002) and with arch type (p=0.00) and in the 1st quadrant (p<0.035). Within the limits of the study the most commonly extracted teeth was the primary upper central incisor high frequency in the maxillary arch. Boys were more affected than girls and most of the extractions were done at 5 years of age.